Reducing speeding via inanimate police presence: An evaluation of a police‐directed field study regarding motorist behavior. Issue 3 (21st July 2020) - Simpson, Rylan; McCutcheon, Mark; Lal, Darryl
Abstract : Research Summary: The present research uses data from a police‐directed field study to explore the effects of police presence on speeding in two large cities in British Columbia, Canada. As part of the study, an inanimate but realistic‐appearing police cut‐out ("Constable Scarecrow") was strategically positioned along roadways while motorist speed was measured using a radar‐recording device. The analyses of the multisite evaluation reveal that the presence of the cut‐out can reduce speeding when deployed along arterial roadways. Policy Implications: Traffic collisions are a leading cause of death and nonfatal injuries for people worldwide. A well‐documented contributor to traffic collisions is speed. Controlling speed has thus become a priority for government, police, and community groups across the world. The findings from the present research demonstrate that police can reduce speeding via their inanimate presence. This is the first known study to evaluate the effects of an inanimate but realistic‐appearing police cut‐out on motorist behavior: a sustainable, low‐cost, and easily implementable intervention for communities of all sizes in all places.